Screening for cold tolerance resources in maize seedlings and analysis of leaf cell responses - Hu, Mengting; Zhang, Dan; Du, Wentao; Tian, Huijuan; Hao, Ying; Ding, Shuqi; Yang, Kaizhi; Xu, Ruohang; Zhang, Lei (Frontiers in Plant Science, 2025)
Using 63 maize varieties as materials, this study employed indoor low-temperature stress testing methods to evaluate cold tolerance during the seedling stage. The aim was to investigate the low-temperature resistance of different maize varieties during the seedling stage and to conduct photosynthetic physiological analysis and leaf cell responses for extreme materials. The results of the experiment indicate that: (1) Different maize varieties exhibit variations in cold tolerance during the seedling stage, and the extent to which various measurement indicators are affected by low-temperature stress differs. (2) The comparative analysis of phenotypic traits and physiological indexes showed that low temperature stress inhibited the growth of plant height and stem diameter, and had a great impact on leaf width and leaf area. The relative conductivity and MDA content showed an upward trend and showed a very significant difference. (3) Correlation analysis shows that phenotypic traits and physiological indicators under normal temperature and low-temperature stress have different correlations. (4) Principal component analysis (PCA) transformed the 12 measurement indicators into 7 independent indicators, with a cumulative contribution rate of 87.12%. Leaf area, SOD, stem thickness, relative conductivity, proline content, CAT, and chlorophyll content were identified as the primary evaluation indicators for cold resistance in maize seedlings. (5) Using the membership function method combined with cluster analysis, the cold tolerance of the 63 maize varieties was classified into five categories: extremely strong cold tolerance, strong cold tolerance, moderate cold tolerance, weak cold tolerance, and cold-sensitive. Based on the ranking by D value, two extreme materials were identified: the variety with extremely strong cold tolerance is No. 11 (Jiuyang 818), and the cold-sensitive variety is No. 6 (JR288). (6) Phenotypic observations and measurements of photosynthetic physiological indicators in the two extreme materials revealed that the variety with extremely strong cold tolerance, Jiuyang 818, exhibited more robust plant growth and stronger photosynthetic capacity. (7) Cytological observations of maize leaves revealed that Jiuyang 818 exhibited best cold tolerance during the low temperature stress phase, but JR288 showed significant wilting of leaves six days after low-temperature stress. This finding is consistent with the phenotypic observations and photosynthetic physiological determination results obtained in the preliminary studies. Through indoor identification methods, this study screened and characterized different maize varieties to identify cultivars with varying levels of low-temperature tolerance. The research elucidates the effects of low-temperature stress on photosynthetic physiology and associated changes in leaf cellular structure. These results may provide theoretical references for future studies on low-temperature stress tolerance.